About Being-Together With As a Sociocultural Tendency and Creative Collectives: an interdisciplinary proposal of methodology for identifying trends for future scenarios (ModaPalavra e-periódico, 2018)
This article focuses on a proposal for a methodology to identify sociocultural trends and their consequences. To develop this objective, we approach the understanding of trends, especially from a sociological perspective. In opening this perspective, we introduce our understanding that sociocultural tendencies are social sensitivities, and thus establish the principles for the emergence of social forms, values, and other tendencies. The understanding of this relationship is essential because it leads us to address the correspondence between the object of study of this research - the Creative Collectives - and the sociocultural tendency being-together-with. Having established the connections between these instances, the work addresses the immanent relationship among them and the emergence of the creative economy also treated here as the economy of culture. After weaving these affinities, we present the future scenarios tool and locate its use in the methodological proposal that we deploy. This proposal is based on principles of comprehensive sociology, interpretive anthropology, and Dialogism, having in the future scenarios a visualization mechanism, through narrative, of development for elements identified in loco in Creative Collectives of the city of Porto Alegre.
Keywords: sociocultural tendencies; creative collectives; creative economy; future scenarios